Golf my own damn way : a real guy's guide to chopping ten strokes off your score - Daly, John, 1966-; Waggoner, Glen (New York : Harper, 2007)
A record-setting professional golfer outlines his offbeat, fun-oriented philosophy to golf play, discussing such challenges as high winds, limited practice times, and playing with hangovers
Keywords: Swing (Golf); Putting (Golf); Golf